Emerging Trends in Early Childhood Science Education: Pedagogies and Insights from a Systematic Literature Review - Rika Partikasari; Nina Kurniah; Didik Suryadi; Muhammad Kristiawan (Yayasan Darussalam Bengkulu, 2026)
The purpose of this study is to systematically identify and analyze global research trends in early childhood science education for children aged 3-8 years, focusing on prevalent instructional approaches and their effectiveness. A systematic literature review was conducted following the PRISMA guidelines. The Scopus database was queried for relevant, accredited articles published between 2015 and 2025. After applying strict inclusion criteria, a final corpus of seven key publications was selected for in-depth qualitative analysis to identify dominant themes and patterns. This review provides a synthesized analysis of the most recent and impactful pedagogical strategies in early childhood science education. It confirms the dominance of concrete, experience-based learning and reveals the significant effectiveness of role-playing and multimodal visualization techniques in making abstract scientific concepts accessible to young learners. A key novel insight is the identification of critical contextual factors for successful implementation, highlighting that teacher acceptance of new methodologies is highest when they align with existing pedagogical values and daily practices. Furthermore, the study underscores the influential role of the teacher and the intentional design of the learning environment in fostering scientific engagement. The primary contribution is a clear, evidence-based argument for developing holistic, play-based, and contextually relevant curricula. These findings offer a foundational framework for educators, researchers, and policymakers to design effective, developmentally appropriate, and engaging science learning strategies for the modern era.